No clinically meaningful difference in 1-year patient-reported outcomes among major approaches for primary total hip arthroplasty. Issue 5 (September 2022) - ,; Bircher, James B; Kamath, Atul F; Piuzzi, Nicolas S; Barsoum, Wael K; Brooks, Peter J; Hampton, Robert J; Higuera, Carlos A; Klika, Alison; Krebs, Viktor E; Mesko, Nathan W; Molloy, Robert M; et al.
Background: Debate continues around the most effective surgical approach for primary total hip arthroplasty (THA). This study's purpose was to compare 1-year patient-reported outcome measures (PROMs) of patients who underwent direct anterior (DA), transgluteal anterolateral (AL)/direct lateral (DL), and posterolateral (PL) approaches. Methods: A prospective consecutive series of primary THA for osteoarthritis ( n = 2390) were performed at 5 sites within a single institution with standardised care pathways (20 surgeons). Patients were categorised by approach: DA ( n = 913; 38%), AL/DL ( n = 505; 21%), or PL ( n = 972; 41%). Primary outcomes were pain, function, and activity assessed by 1-year postoperative PROMs. Multivariable regression modeling was used to control for differences among the groups. Wald tests were performed to test the significance of select patient factors and simultaneous 95% confidence intervals were constructed. Results: At 1-year postoperative, PROMs were successfully collected from 1842 (77.1%) patients. Approach was a statistically significant factor for 1-year HOOS pain ( p = 0.002). Approach was not a significant factor for 1-year HOOS-PS ( p = 0.16) or 1-year UCLA activity ( p = 0.382). Pairwise comparisons showed no significant difference in 1-year HOOS pain scores between DA and PL approach ( p > 0.05). AL/DL approach had lower (worse) pain scores than DA or PL approaches with differences in adjusted median score of 3.47 and 2.43, respectively ( p < 0.05). Conclusions: Patients receiving the AL/DL approach had a small statistical difference in pain scores at 1 year, but no clinically meaningful differences in pain, activity, or function exist at 1-year postoperative.